2019
DOI: 10.1136/bmjresp-2018-000393
|View full text |Cite
|
Sign up to set email alerts
|

Chest radiograph reading panel performance in a Bangladesh pneumococcal vaccine effectiveness study

Abstract: IntroductionTo evaluate WHO chest radiograph interpretation processes during a pneumococcal vaccine effectiveness study of children aged 3–35 months with suspected pneumonia in Sylhet, Bangladesh.MethodsEight physicians masked to all data were standardised to WHO methodology and interpreted chest radiographs between 2015 and 2017. Each radiograph was randomly assigned to two primary readers. If the primary readers were discordant for image interpretability or the presence or absence of primary endpoint pneumon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The World Health Organization (WHO) methodology for classifying pediatric chest radiographs, developed in 1997, has been applied to efficacy and effectiveness studies of bacterial conjugate vaccines as well as more recently to epidemiological research of pediatric lower respiratory infections [7][8][9][10][11][12][13][14][15][16]. This methodology aims to identify chest radiographs that have a higher probability of bacterial etiology, with an emphasis on Streptococcus pneumoniae and Haemophilus influenzae, and prioritizes both interobserver reliability and specificity [8,15].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) methodology for classifying pediatric chest radiographs, developed in 1997, has been applied to efficacy and effectiveness studies of bacterial conjugate vaccines as well as more recently to epidemiological research of pediatric lower respiratory infections [7][8][9][10][11][12][13][14][15][16]. This methodology aims to identify chest radiographs that have a higher probability of bacterial etiology, with an emphasis on Streptococcus pneumoniae and Haemophilus influenzae, and prioritizes both interobserver reliability and specificity [8,15].…”
Section: Introductionmentioning
confidence: 99%
“…Higher interoperator and interrater reliability for LUS interpretation than for CXR interpretation in identifying pediatric pneumonia is supported by the literature (Figure 4). 14,16–33 We contrasted kappas observed in this study with kappas observed in the literature among other LUS and CXR interpreters. Kappas between LUS interpreters were 0.900 (in Pakistan) and 0.917 (in Mozambique) in this study (expert LUS interpreters) and ranged from 0.635 to 0.930 in the literature, whereas kappa between CXR interpreters ranged from −0.04 to 0.62 in this study and from 0.35 to 0.74 in the literature.…”
Section: Discussionmentioning
confidence: 56%
“…Instead, we are using chest radiography in India, and applying rigorous methodology developed and validated by the WHO CRES working group [34]. Our group has substantial experience using the WHO chest radiograph interpretation, and we will utilise chest radiography in Guatemala, Peru, and Rwanda when lung ultrasound is not obtained [35].…”
Section: Discussionmentioning
confidence: 99%